Reconstruction of Niet Ontvankelijke Verklaard Verdict In the Law of Civil Procedure as a Manifestation of Fast, Simple, Low Cost and Complete Principle of Justice - Samsiati, Samsiati (Universitas Airlangga, 2022)
Dispute resolution through court is more favorable because the binding decisions of judges can resolve cases. This study discusses ratio legis of niet ontvankelijke verklaard in the law of civil procedure and in the formulation of the delimitation of the judge in giving niet ontvankelijke verklaard in the fast, simple, low cost, and complete settlement of civil disputes. This study used legal research methods with legislation and conceptual approaches. The result of the study showed that The limitation of the judge in examining the lawsuit that does not meet the formal requirements and decides the lawsuit is inadmissible (niet onvankelijk verklaard), in the absence of fast, simple, low-cost, and complete civil disputes, as stated in the Draft Bill of the Law of Civil Procedure, which is essentially related to the types of exceptions that can become the basis for the judge in determining the lawsuit to be inadmissible (niet onvankelijk verklaard). Indonesia's current civil procedure laws, HIR and RBg, do not specifically outline the standards that a judge must employ to declare that a matter is inappropriate for filing (niet onvankelijk verklaard). Before making a ruling that is not admissible (niet onvankelijk verklaard) in the settlement, the judge must be aware of his or her restrictions in this situation. As stated in the Draft Bill of the Law of Civil Procedure, the judge is limited in examining lawsuits that do not meet the formal requirements and deciding that the lawsuit is inadmissible (niet onvankelijk verklaard), in the absence of quick, easy, inexpensive, and comprehensive civil disputes. This limitation is essentially related to the types of exceptions that can become the basis for the judge in determining that the lawsuit is inadmissible (niet onvankelijk verklaard)